Development of Electronic Student Worksheets (E-LKPD): A Scientific Approach Based on Discovery Learning in Natural Science Learning - Saripahyani Siregar; Abdul Hamid K; Farihah Farihah (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of this research and development is to produce E-LKPD learning media with a scientific approach based on discovery learning in science that is feasible, practical, and effective. The type of research is the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The research results show: (1) The Media Expert validation test obtained an average result of 87% in the very good category; (2) The Material Expert validation test obtained an average result of 96% in the very good category; and (3) The Design Expert validation test Instructional results obtained an average of 93% in the very good category; (4) individual trials obtained an average result of 91% in the very good category; (5) small group trials obtained an average result of 90% in the very good category; (6) field group trials obtained an average result of 89% in the very good category; and (7) practicality tests for teachers obtained an average result of 90% in the very good category, while practicality tests for students obtained an average result of 93% in the in the very good category. For the results of using E-LKPD with a scientific approach based on discovery learning, the experimental class obtained an average learning outcome value of 78, while the control class obtained an average learning outcome value of 72. Hypothesis testing used an independent sample T-test with a 2-tailed sig result of 0.000 < 0.05. This shows that students who use E-LKPD Discovery Learning have higher learning outcomes with a confidence level of 95%